Preparation method and application of lithium ion battery biogum-based binder
By esterification modification of biogems, the problems of high cost, poor affinity and strong water absorption of lithium-ion batteries are solved, and the cost reduction and electrochemical performance of lithium-ion batteries are achieved.
Patent Information
- Application Number
- CN202510102800.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-15
AI Technical Summary
The binder of existing lithium-ion batteries is expensive, the preparation process is complex, the affinity is poor and the water absorption is strong, resulting in poor electrochemical performance.
Low-cost, easy-to-industrial bioglue is used as raw materials to esterification and modification with organic acids to improve the elasticity and tensile properties of the bioglue, improve the affinity with the electrode material, and reduce water absorption.
Significantly reduce the cost of lithium-ion battery preparation, improve the hydrophilicity and thermal stability of biogels, enhance the cycle stability of the battery, and realize the high-value utilization of biogels.
Smart Images

Figure CN119823667A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a preparation method and application of a biological glue-based binder for lithium ion batteries. Background Art
[0002] With the increasing depletion of traditional fossil energy and the associated environmental issues, the demand for renewable energy is becoming increasingly urgent. However, most energy sources, such as solar, tidal and wind energy, are limited due to their inherent intermittent and unstable nature. Therefore, large-scale electrochemical energy storage technology is considered a reliable candidate for the efficient storage of such energy. Among various rechargeable batteries, lithium-ion batteries are considered a mature form of technology due to their popularity in portable electronic devices and electric vehicles. In lithium-ion batteries, electrodes are usually assembled using active materials, conductive materials, binders and metal current collectors. Binders can promote the cohesion of particles in the electrode and also ensure that the slurry has good viscosity to achieve uniform coating and adhesion to the metal current collector. In addition, binders promote the transfer of lithium ions and have an impact on the electrochemical stability and specific capacity of the battery.
[0003] At present, the conventional binder for the positive electrode in commercial lithium-ion batteries is PVDF, which is expensive and will swell in the electrolyte. In addition, PVDF needs to be dissolved in an organic solvent, usually N-methylpyrrolidone, to produce a slurry for the coating process. N-methylpyrrolidone is an expensive and toxic organic solvent that is harmful to both the human body and the environment. The negative electrode binders of lithium-ion batteries are mainly CMC and SBR binders, which are widely used as graphite negative electrodes. They are expensive, but they show poor electrochemical performance when used for silicon-carbon negative electrodes. Therefore, it is necessary to develop alternative binders that are fluorine-free, low-cost and more environmentally friendly. Renewable bio-glue binders have been developed for battery binders. When used as battery negative electrode binders, they have poor performance with graphite negative electrodes and silicon-carbon negative electrodes due to their high hydroxyl content and poor affinity with carbon; when used as battery positive electrode binders, they have poor performance because the polyhydroxy structure of bio-glue is highly hydrophilic and will adsorb a small amount of water, which will cause electrolyte decomposition and deterioration of electrochemical performance during battery cycling. Therefore, it is necessary to modify the bio-glue binder so that it can be widely used as a binder for the positive and negative electrodes of batteries. Summary of the invention
[0004] In view of the problems of high cost, complex preparation process, poor affinity with electrode materials, strong water absorption and the like of lithium battery binders, the present invention provides a preparation method and application of a biological glue-based binder for lithium ion batteries. Low-cost and easily industrialized biological glue is used as a raw material, and esterification modification is performed with an organic acid to give the biological glue elasticity and tensile properties. It is used in lithium battery binders to solve the problem of high cost of lithium battery binders. The presence of ester bonds can effectively improve the affinity of the biological glue binder with the electrode material, and at the same time can reduce the water absorption of the binder, so that the biological glue-based binder can be widely used as a positive and negative electrode binder for batteries, broadening the application prospects of biological glue in lithium battery binders.
[0005] To achieve the above technical objectives, the technical solution of the present invention is as follows:
[0006] In one aspect, the present invention provides a method for preparing a bio-gum-based binder for lithium batteries, the method comprising the following steps:
[0007] (1) Mix the bio-glue and the organic acid evenly;
[0008] (2) The mixture obtained in step (1) is uniformly mixed with a dispersant to carry out an esterification reaction, and then dried to obtain the bio-gum-based adhesive.
[0009] Preferably, the biological glue is one or more of spiny bean gum, fenugreek gum, guar gum, sodium alginate, carob gum, konjac gum and gum arabic.
[0010] Preferably, the organic acid is one or more of propionic acid, butyric acid, acetic acid, terephthalic acid and citric acid.
[0011] Preferably, the mass ratio of the bio-gum to the organic acid is (2:1)-(10:1).
[0012] Preferably, in step (1), the uniform mixing is performed by one or more of grinding, stirring and ball milling.
[0013] Preferably, in step (2), the dispersant is one or more of water, glycerol, and a metal salt solution with a concentration of 0.1-1M; the metal salt includes one or more of sodium salt, potassium salt, magnesium salt, calcium salt, and aluminum salt.
[0014] Preferably, the drying treatment is one or more of heating and stirring, freeze drying, and vacuum drying.
[0015] Another aspect of the present invention provides an electrode sheet, wherein the electrode sheet is obtained by coating a slurry containing an electrode active material, a conductive agent and a binder on a current collector, wherein the binder is prepared by the above-mentioned preparation method. When the electrode active material is a positive electrode active material, the electrode sheet is a positive electrode sheet; when the electrode active material is a negative electrode active material, the electrode sheet is a negative electrode sheet.
[0016] Preferably, the mass percentage of the binder in the electrode sheet is 0.5%-20%.
[0017] The present invention also provides a lithium ion battery, which comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet and / or the negative electrode sheet is the above-mentioned electrode sheet.
[0018] The beneficial effects of the present invention are:
[0019] The bio-glue used in the method of the present invention has the characteristics of abundant reserves, renewability, low cost, etc., and can significantly reduce the preparation cost of lithium-ion batteries. At the same time, the bio-glue is non-toxic and harmless to the human body and the environment, has good solubility in cold water, and exhibits good viscosity at 25°C, so no additional additives are required during use.
[0020] The present invention utilizes organic acid to esterify the bio-glue to improve its affinity with electrode materials, enhance hydrophobic properties, improve the elasticity and plasticity of the bio-glue, ensure good tensile properties, and have better thermal stability and chemical stability. Lithium-ion batteries using the organic acid-modified bio-glue as a binder show excellent cycle stability, thereby achieving high-value utilization of the bio-glue. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The cycle efficiency diagram of the half-cell assembled with the negative electrode sheet prepared in Comparative Example 1;
[0022] Figure 2 The cycle efficiency diagram of the half-cell assembled with the positive electrode sheet prepared in Comparative Example 2;
[0023] Figure 3 The cycle efficiency diagram of the half-cell assembled with the negative electrode sheet prepared in Example 1;
[0024] Figure 4 The cycle efficiency diagram of the half-cell assembled with the negative electrode sheet prepared in Example 2;
[0025] Figure 5 This is a cycle efficiency diagram of a half-cell assembled with the negative electrode sheet prepared in Example 3;
[0026] Figure 6 Cycle efficiency diagram of the negative electrode sheet assembled half-cell prepared in Example 4;
[0027] Figure 7 Cycle efficiency diagram of the negative electrode sheet assembled half-cell prepared in Example 5;
[0028] Figure 8 This is a cycle efficiency diagram of a half-cell assembled with the negative electrode sheet prepared in Example 6;
[0029] Fig. 9 This is a cycle efficiency diagram of a half-cell assembled with the negative electrode sheet prepared in Example 7;
[0030] Fig.10 This is a cycle efficiency diagram of a half-cell assembled with the negative electrode sheet prepared in Example 8;
[0031] Fig.11 This is a cycle efficiency diagram of a half-cell assembled with the negative electrode sheet prepared in Example 9;
[0032] Fig.12 This is a cycle efficiency diagram of a half-cell assembled with the positive electrode sheet prepared in Example 10;
[0033] Fig.13 The tensile diagram comparison results of the propionic acid-spiny bean gum adhesive and pure spiny bean gum prepared in Examples 1-3 are shown;
[0034] Fig.14 The contact angle test results of the propionic acid-spiny bean gum adhesive and pure spiny bean gum prepared in Example 1 and water are compared, a is Example 1, and b is pure spiny bean gum. DETAILED DESCRIPTION
[0035] The present invention is described in detail below through specific examples. However, the present invention is not limited to the following examples, and the implementation conditions used in the examples can be further adjusted according to different requirements of specific use, and the technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.
[0036] Comparative Example 1
[0037] (1) Weigh 0.24 g of silicon-carbon alloy negative electrode material (Crode, Si-C950-K), 0.08 g of acetylene black, and 0.08 g of PVDF (Crode, PVDF 5130) in a mortar, mix well, and grind for 30 min;
[0038] (2) Add 9 g of solvent N-methylpyrrolidone to the mixture obtained in step (1) to obtain a negative electrode slurry, continue grinding until it is uniform, apply it on a copper foil using a 150 μm scraper, and vacuum dry it at 80° C. for 12 h to obtain a negative electrode sheet.
[0039] The half-cell was assembled in the order of negative electrode shell, spring, gasket, lithium sheet (diameter 16mm), 3501 diaphragm (Crode), and negative electrode sheet. The electrolyte used for the negative electrode was LX-025 (Duoduo Chemical Reagent). The assembled half-cell was tested at a current density of 0.1C. The test results are shown in the figure. Figure 1 shown.
[0040] Comparative Example 2
[0041] Comparative Example 2 adopts the same electrode preparation method as Comparative Example 1, except that lithium phosphate (LFP) positive electrode material (Croode, lithium iron phosphate (D-3)) is used to prepare the positive electrode.
[0042] The half-cell was assembled in the order of positive electrode shell, spring, gasket, lithium sheet (diameter 16mm), 3501 diaphragm (Crode), and positive electrode sheet. The electrolyte used for the positive electrode was LX-014 (Duoduo Chemical Reagent). The assembled half-cell was tested at a current density of 0.1C. The test results are shown in the figure. Figure 2 shown.
[0043] Example 1
[0044] (1) Mix 0.08 g of spiny bean gum with 35 μL of propionic acid, grind evenly and set aside;
[0045] (2) mixing the mixed powder and water uniformly, heating and stirring at 80° C. for 8 hours to obtain propionic acid-spiny bean gum binder powder;
[0046] (3) Weigh 0.24 g of silicon-carbon alloy negative electrode and 0.08 g of acetylene black, mix and grind for 10 min, then add the binder in the above (2), mix and grind for 10 min, then slowly add deionized water dispersant and stir until the slurry becomes a slurry, continue grinding and mixing for 30 min, and after obtaining a uniform slurry, use a 150 μm scraper to apply it on a copper foil, and vacuum dry it at 80°C for 12 h to obtain a negative electrode sheet.
[0047] The half-cell was assembled in the order of negative electrode shell, spring, gasket, lithium sheet (diameter 16mm), 3501 diaphragm (Crode), and negative electrode sheet. The electrolyte used for the negative electrode was LX-025 (Duoduo Chemical Reagent). The assembled half-cell was tested at a current density of 0.1C. The test results are shown in the figure. Figure 3 shown.
[0048] Example 2
[0049] (1) Mix 0.08 g of spiny bean gum with 25 μL of propionic acid, stir magnetically and set aside;
[0050] (2) mixing the mixed powder and water uniformly, heating and stirring at 80° C. for 8 hours, and freeze-drying to obtain propionic acid-spiny bean gum binder powder;
[0051] (3) Weigh 0.24 g of silicon-carbon alloy negative electrode and 0.08 g of acetylene black, mix and grind for 10 min, then add the binder in the above (2), mix and grind for 10 min, then slowly add deionized water dispersant and stir until the slurry becomes a slurry, continue grinding and mixing for 30 min, and after obtaining a uniform slurry, use a 150 μm scraper to apply it on a copper foil, and vacuum dry it at 80°C for 12 h to obtain a negative electrode sheet.
[0052] The half-cell was assembled in the order of negative electrode shell, spring, gasket, lithium sheet (diameter 16mm), 3501 diaphragm (Crode), and negative electrode sheet. The electrolyte used for the negative electrode was LX-025 (Duoduo Chemical Reagent). The assembled half-cell was tested at a current density of 0.1C. The test results are shown in the figure. Figure 4 shown.
[0053] Example 3
[0054] (1) Mix 0.08 g of spiny bean gum with 45 μL of propionic acid, and then ball-mill until uniform.
[0055] (2) mixing the mixed powder and water uniformly, heating and stirring at 80° C. for 8 hours, and freeze-drying to obtain propionic acid-spiny bean gum binder powder;
[0056] (3) Weigh 0.24 g of silicon-carbon alloy negative electrode and 0.08 g of acetylene black, mix and grind for 10 min, then add the binder in the above (2), mix and grind for 10 min, then slowly add deionized water dispersant and stir until the slurry becomes a slurry, continue grinding and mixing for 30 min, and after obtaining a uniform slurry, use a 150 μm scraper to apply it on a copper foil, and vacuum dry it at 80°C for 12 h to obtain a negative electrode sheet.
[0057] The half-cell was assembled in the order of negative electrode shell, spring, gasket, lithium sheet (diameter 16mm), 3501 diaphragm (Crode), and negative electrode sheet. The electrolyte used for the negative electrode was LX-025 (Duoduo Chemical Reagent). The assembled half-cell was tested at a current density of 0.1C. The test results are shown in the figure. Figure 5 shown.
[0058] Example 4
[0059] (1) 0.08 g of spiny bean gum and 35 μL of propionic acid were directly mixed in a ratio of 1:1 and 2:1, respectively, and magnetically stirred for use;
[0060] (2) mixing the mixed powder and glycerin uniformly, heating and stirring at 80° C. for 8 hours, and freeze-drying to obtain propionic acid-spiny bean gum binder powder;
[0061] (3) Weigh 0.24 g of silicon-carbon alloy negative electrode and 0.08 g of acetylene black, mix and grind for 10 min, then add the binder in the above (2), mix and grind for 10 min, then slowly add glycerol dispersant and stir until the slurry becomes a slurry, continue grinding and mixing for 30 min, and after obtaining a uniform slurry, use a 150 μm scraper to apply it on a copper foil, and vacuum dry it at 80°C for 12 h to obtain a negative electrode sheet.
[0062] The half-cell was assembled in the order of negative electrode shell, spring, gasket, lithium sheet (diameter 16mm), 3501 diaphragm (Crode), and negative electrode sheet. The electrolyte used for the negative electrode was LX-025 (Duoduo Chemical Reagent). The assembled half-cell was tested at a current density of 0.1C. The test results are shown in the figure. Figure 6 shown.
[0063] Example 5
[0064] (1) Mix 0.08 g of spiny bean gum with 35 μL of propionic acid, stir magnetically and set aside;
[0065] (2) mixing the mixed powder with a 0.5 M sodium chloride solution, heating and stirring at 80° C. for 8 hours, and freeze-drying to obtain a propionic acid-spiny bean gum binder powder;
[0066] (3) Weigh 0.24 g of silicon-carbon alloy negative electrode and 0.08 g of acetylene black, mix and grind for 10 min, then add the binder in (2) above, mix and grind for 10 min, then slowly add sodium chloride solution dispersant and stir until the slurry becomes a slurry, continue grinding and mixing for 30 min, after obtaining a uniform slurry, use a 150 μm scraper to apply it on a copper foil, and vacuum dry it at 80°C for 12 h to obtain a negative electrode sheet.
[0067] The half-cell was assembled in the order of negative electrode shell, spring, gasket, lithium sheet (diameter 16mm), 3501 diaphragm (Crode), and negative electrode sheet. The electrolyte used for the negative electrode was LX-025 (Duoduo Chemical Reagent). The assembled half-cell was tested at a current density of 0.1C. The test results are shown in the figure. Figure 7 shown.
[0068] Example 6
[0069] (1) Mix 0.08 g guar gum with 35 μL propionic acid, grind evenly and set aside;
[0070] (2) mixing the mixed powder and water uniformly, and drying under vacuum at 80° C. for 8 hours to obtain propionic acid-guar gum binder powder;
[0071] (3) Weigh 0.24 g of silicon-carbon alloy negative electrode and 0.08 g of acetylene black, mix and grind for 10 min, then add the binder in the above (2), mix and grind for 10 min, then slowly add deionized water dispersant and stir until the slurry becomes a slurry, continue grinding and mixing for 30 min, and after obtaining a uniform slurry, use a 150 μm scraper to apply it on a copper foil, and vacuum dry it at 80°C for 12 h to obtain a negative electrode sheet.
[0072] The half-cell was assembled in the order of negative electrode shell, spring, gasket, lithium sheet (diameter 16mm), 3501 diaphragm (Crode), and negative electrode sheet. The electrolyte used for the negative electrode was LX-025 (Duoduo Chemical Reagent). The assembled half-cell was tested at a current density of 0.1C. The test results are shown in the figure. Figure 8 shown.
[0073] Example 7
[0074] (1) Mix 0.08 g of fenugreek gum with 35 μL of propionic acid, grind evenly and set aside;
[0075] (2) mixing the mixed powder and water uniformly, heating and stirring at 80° C. for 8 hours, and freeze-drying to obtain propionic acid-fenugreek gum binder powder;
[0076] (3) Weigh 0.24 g of silicon-carbon alloy negative electrode and 0.08 g of acetylene black, mix and grind for 10 min, then add the binder in the above (2), mix and grind for 10 min, then slowly add deionized water dispersant and stir until the slurry becomes a slurry, continue grinding and mixing for 30 min, and after obtaining a uniform slurry, use a 150 μm scraper to apply it on a copper foil, and vacuum dry it at 80°C for 12 h to obtain a negative electrode sheet.
[0077] The half-cell was assembled in the order of negative electrode shell, spring, gasket, lithium sheet (diameter 16mm), 3501 diaphragm (Crode), and negative electrode sheet. The electrolyte used for the negative electrode was LX-025 (Duoduo Chemical Reagent). The assembled half-cell was tested at a current density of 0.1C. The test results are shown in the figure. Fig. 9 shown.
[0078] Example 8
[0079] (1) Mix 0.08 g of spiny bean gum and 35 μL of phthalic acid, stir, grind evenly and set aside;
[0080] (2) mixing the mixed powder and water uniformly, heating and stirring at 80° C. for 8 hours, and freeze-drying to obtain terephthalic acid-spiny bean gum binder powder;
[0081] (3) Weigh 0.24 g of silicon-carbon alloy negative electrode and 0.08 g of acetylene black, mix and grind for 10 min, then add the binder in the above (2), mix and grind for 10 min, then slowly add deionized water dispersant and stir until the slurry becomes a slurry, continue grinding and mixing for 30 min, and after obtaining a uniform slurry, use a 150 μm scraper to apply it on a copper foil, and vacuum dry it at 80°C for 12 h to obtain a negative electrode sheet.
[0082] The half-cell was assembled in the order of negative electrode shell, spring, gasket, lithium sheet (diameter 16mm), 3501 diaphragm (Crode), and negative electrode sheet. The electrolyte used for the negative electrode was LX-025 (Duoduo Chemical Reagent). The assembled half-cell was tested at a current density of 0.1C. The test results are shown in the figure. Fig.10 shown.
[0083] Example 9
[0084] (1) Mix 0.08 g of spiny bean gum and 35 μL of citric acid, stir, grind evenly and set aside;
[0085] (2) mixing the mixed powder and water uniformly, heating and stirring at 80° C. for 8 hours, and freeze-drying to obtain citric acid-spiny bean gum binder powder;
[0086] (3) Weigh 0.24g of silicon-carbon alloy negative electrode and 0.08g of acetylene black, mix and grind for 10min, then add the binder in (2) above, mix and grind for 10min, then slowly add deionized water dispersant and stir until the slurry is slurried, continue grinding and mixing for 30min, and after obtaining a uniform slurry, use a 150μm scraper to apply it on a copper foil, and vacuum dry it at 80℃ for 12h to obtain a negative electrode sheet. Assemble the half-cell in the order of negative electrode shell, spring, gasket, lithium sheet (diameter 16mm), 3501 diaphragm (Croode), and negative electrode sheet. The electrolyte used for the negative electrode is LX-025 (Duoduo Chemical Reagent). The assembled half-cell was tested at a current density of 0.1C. The test results are as follows: Fig.11 shown.
[0087] Example 10
[0088] Example 10 uses the same electrode preparation method as Example 1, except that a lithium phosphate positive electrode material (Crode, lithium iron phosphate (D-3)) is used to prepare the positive electrode sheet, and the half-cell is assembled in the order of positive electrode shell, spring, gasket, lithium sheet (diameter 16mm), 3501 diaphragm (Crode), and positive electrode sheet. The electrolyte used for the positive electrode is LX-014 (Duoduo Chemical Reagent). The assembled half-cell is tested at a current density of 0.1C, and the test results are as follows: Fig.12 shown.
[0089] By comparing Comparative Example 1 with Examples 1-9, the performance of the pole pieces prepared in Examples 1-9 is significantly better than that in the comparative example. Figure 1 As shown in the figure, the silicon-carbon negative electrode prepared in Comparative Example 1 maintained a capacity of 267 mAh g after 200 cycles. -1 , the first effect is 68%. Figure 3 As shown, the silicon-carbon negative electrode sheet prepared in Example 1 was cycled 200 times, with a capacity retention rate of 84% and a capacity of 809 mAh g -1 , the first effect is 82%. Figure 4 As shown, the silicon-carbon negative electrode sheet prepared in Example 2 was cycled 200 times with a capacity retention rate of 80% and a capacity of 720 mAh g -1 , the first effect is 78%. Figure 5 As shown, the silicon-carbon negative electrode sheet prepared in Example 3 was cycled 200 times with a capacity retention rate of 80% and a capacity of 700 mAh g -1 , the first effect is 76%. Figure 6 As shown, the silicon-carbon negative electrode sheet prepared in Example 4 was cycled 200 times, with a capacity retention rate of 82% and a capacity of 770 mAh g -1 , the first effect is 80%. Figure 7 As shown, the silicon-carbon negative electrode sheet prepared in Example 5 was cycled 200 times with a capacity retention rate of 79% and a capacity of 741 mAh g -1 , the first effect is 81%. Figure 8 As shown, the silicon-carbon negative electrode sheet prepared in Example 6 was cycled 200 times, with a capacity retention rate of 83% and a capacity of 780 mAh g -1 , the first effect is 82%. Fig. 9 As shown, the silicon-carbon negative electrode sheet prepared in Example 7 was cycled 200 times with a capacity retention rate of 86% and a capacity of 783 mAh g -1 , the first effect is 80%. Fig.10 As shown, the silicon-carbon negative electrode sheet prepared in Example 8 was cycled 200 times, with a capacity retention rate of 88% and a capacity of 800 mAh g -1 , the first effect is 83%. Fig.11 As shown, the silicon-carbon negative electrode sheet prepared in Example 9 was cycled 200 times with a capacity retention rate of 85% and a capacity of 808 mAh g -1 , the initial effect is 75%.
[0090] like Fig.12 As shown, the lithium iron phosphate positive electrode prepared in Example 10 was cycled 200 times, with a capacity retention rate of 70% and a capacity maintained at 115 mAh g -1 , the first efficiency is 90%, which proves the feasibility of the application of the present invention on the positive electrode sheet.
[0091] The propionic acid-spiny bean gum binder powders prepared in Examples 1-3 were dissolved in water, poured into a mold, and dried to obtain propionic acid-spiny bean gum films. The pure spiny bean gum films were used as control tests to perform tensile performance tests. Fig.13 As shown, the elongation at break of Example 1 is 136%, that of Example 2 is 167%, and that of Example 3 is 157%. Compared with the spiny bean gum film, the elasticity and tensile properties are significantly improved.
[0092] like Fig.14 As shown, the contact angle test was performed on the propionic acid-spiny bean gum film prepared in Example 1. Compared with the pure spiny bean gum film, the hydrophobic property was significantly improved.
[0093] The above embodiments are only preferred embodiments of the present invention and are not intended to limit the implementation methods. The protection scope of the present invention shall be subject to the scope defined in the claims. Other different forms of changes or modifications may be made based on the above description. Obvious changes or modifications derived therefrom are still within the protection scope of the present invention.
Claims
1. A method for preparing a bio-glue-based binder for lithium batteries, characterized in that: The method comprises the following steps: (1) Mix the bio-glue and the organic acid evenly; (2) The mixture obtained in step (1) is uniformly mixed with a dispersant to carry out an esterification reaction, and then dried to obtain the bio-gum-based adhesive.
2. The preparation method according to claim 1, characterized in that: The biological glue is one or more of spiny bean gum, fenugreek gum, guar gum, sodium alginate, carob gum, konjac gum and gum arabic.
3. The preparation method according to claim 1, characterized in that: The organic acid is one or more of propionic acid, butyric acid, acetic acid, terephthalic acid and citric acid.
4. The preparation method according to claim 1, characterized in that: The mass ratio of the bio-glue to the organic acid is (2:1)-(10:1).
5. The preparation method according to claim 1, characterized in that: In step (1), the uniform mixing is carried out by one or more of grinding, stirring and ball milling.
6. The preparation method according to claim 1, characterized in that: In step (2), the dispersant is one or more of water, glycerol, and a metal salt solution with a concentration of 0.1-1M.
7. The preparation method according to claim 1, characterized in that: The drying treatment is one or more of heating and stirring, freeze drying, and vacuum drying.
8. An electrode sheet, wherein the electrode sheet is obtained by coating a slurry containing an electrode active material, a conductive agent and a binder on a current collector, wherein the binder is prepared by the preparation method according to any one of claims 1 to 7.
9. The electrode sheet according to claim 8, characterized in that: The mass percentage of the binder in the electrode sheet is 0.5%-20%.
10. A lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet and / or the negative electrode sheet is the electrode sheet according to any one of claims 8 to 9.